Soybean phosphatidylcholine liposomes as model membranes to study lipid peroxidation photoinduced by pterin - Thomas, Andrés Héctor (2016)
Oxidized pterins, efficient photosensitizers under UVA irradiation, accumulate in the skin of patients suffering from vitiligo, a chronic depigmentation disorder. Soybean phosphatidylcholine (SoyPC) liposomes were employed as model membranes to investigate if pterin (Ptr), the parent compound of oxidized pterins, is able to photoinduced lipid peroxidation. Size exclusion chromatography and dialysis experiments showed that Ptr is not encapsulated inside the liposomes and the lipid membrane is permeable to this compound. The formation of conjugated dienes and trienes, upon UVA irradiation, was followed by absorption at 234 and 270 nm, respectively. The photoproducts were characterized by mass spectrometry and oxygenation of SoyPC was demonstrated. In addition, analysis of MS/MS spectra suggested the formation hydroperoxides. Finally, the biological implications of the findings are discussed.